IMPORTANT FEATURES ON IMPROVING THE PRINCIPLES OF HUMANITY AND TOLERANCE OF YOUTH (Scientific journal of the Fergana State University, 2023)
This article discusses the role and place of the ideals of humanism, tolerance and tolerance in the development of ethics, culture, humanistic qualities of young people who are the leading forces of our society.